(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Zingiberaceae (Order: Zingiberales) is recognized as the essential herbaceous species in the tropics. Several species of Zingiberaceae have shown potential in managing some Lepidopteran and Dipteran pests. Currently, there is no report in Malaysia explores the potential use of Zingiberaceae in managing cocoa pests, particularly the Cocoa pod borer (CPB), Conopomorpha cramerella. The study was conducted to evaluate the potential of Zingiberaceae as an adult emergence inhibition of C. cramerella using three locally grown species in Malaysia; Alpinia galanga (galanga), Curcuma longa (turmeric), and Zingiber officinale (ginger). Different ages of the CPB pupa (Days 1, 2, 3, 4, and 5) were selected and were sprayed with Zingiberaceae essential oils (EOs). Pupa was sprayed with EOs at four different concentrations; 100, 200, 400, and 800 ppm. Observations were carried out after 5 to 7 days, where the percentage of the unhatched pupa and healthy adult was recorded. The percentage of the deformed adults were examined based on the abdomen, the antenna, the wings, and overall deformities. The study was repeated four times for each EOs. Results denoted that the percentage of the unhatched pupa was the highest at C. longa (49.75 % a) and significantly different (p<0.05) with A. galanga (48.00 % b), Z. officinale (40.97 % c) and control treatment (13.59 % d). The highest healthy adult emergence was recorded under the control treatment (75.77 % a), and significantly different with all Zingiberaceae EOs. The overall results denoted that most of the deformities occurred after pupa were treated with the Zingiberaceae EOs at high concentrations (400 and 800 ppm), and engaged with the body and wing deformities. The symptom of adult deformities after treating with EOs may indicate the potential of Zingiberaceae as an adult emergence inhibitor of C. cramerella, and can be possibly used for the development of Zingiberaceae based botanical pesticide in the future. J Bangladesh Agril Univ 17(3): 349–354, 2019